Microencapsulation of Curcumin by a Spray-Drying Technique Using Gum Arabic as Encapsulating Agent and Release Studies - Andreea Bucurescu (2018)
Curcumin is a natural yellow pigment extracted from dried roots of turmeric, used in food applications. Despite its applicability in food products, this phenolic compound is also used in the pharmaceutical field. It is reported to have health benefits such as anticancer, antitumor, and antiviral effects. However, curcumin is a very unstable compound. Therefore, this work proposes the microencapsulation of curcumin, in order to protect it and to improve its stability and solubility in water, by spray-drying, using the gum arabic as an encapsulating agent in three different concentrations 10, 15, and 20% (weight/volume (w/v)). Emulsions were prepared with coconut oil and used to prepare the curcumin microparticles. For this purpose, different analysis and studies were performed. A product yield ranging from 44 to 52% and from 29 to 42% was obtained for the production of microparticles without and with curcumin, respectively. The curcumin microcapsules and empty capsules were characterized and evaluated. All the microparticles presented a spherical form, had a diameter around 7-9 gm (considering a volume distribution), and had a rough surface. The efficiency of encapsulation was between 75 and 85%, being higher for the particles prepared with higher concentrations of encapsulating agents. Considering the controlled release studies, the microcapsules were prepared with different concentrations of gum arabic but showed similar release profiles. However, it was also concluded that increasing the amount of gum arabic used in the formulation of the microparticles, the amount of curcumin released in the first minutes decreases; therefore, the release tends to be slower (63.2% of the release varied between 25.5 and 69.0 min). Fitting the experimental results to a linearized equation of the Weibull model, it was possible to obtain a good correlation coefficient (R-2 varying from 0.94 to 0.97), indicating that this model adapts to the experimental data obtained.